Rancang Bangun Sistem Informasi Billing Berbasis Website di Heyklin Laundry Ciparay - Vega Ferdiawan; Nano Suyatna (Jurnal Dimamu, 2022)
The information system currently used at Binar Ilmu Boarding School (BIBS) is still an unintegrated Heyklin Laundry is a business that runs a business in the field of laundry services. Based on a survey that has been conducted so far, Heyklin Laundry does not have its own information system and still uses a manual system, this laundry also does not have an accurate database storage system so all data is still stored in a book. To overcome this problem, an application will be designed that can help the Heyklin Laundry business so that this application can provide from Heyklin Laundry about laundry services offered to customers, facilitate the process of making income reports quickly, precisely and accurately, provide professional service to customers and minimize possible errors.